The invisible world : early modern philosophy and the invention of the microscope - Wilson, Catherine, 1951- (Studies in intellectual history and the history of philosophy., 1995)
Wilson argues that the discovery of the microworld - and the apparent role of living animalcula in generation, contagion, and disease - presented metaphysicians with the task of reconciling the ubiquity of life with human-centered theological systems. It was also a source of problems for philosophers concerned with essences, qualities, and the limits of human knowledge, whose positions are echoed in current debates about realism and instrument-mediated knowledge. Covering the contributions of pioneering microscopists (Leeuwenhoek, Swammerdam, Malpighi, Grew, and Hooke) and the work of philosophers interested in the microworld (Bacon, Descartes, Leibniz, Malebranche, Locke, and Berkeley), she challenges historians who view the abstract sciences as the sole catalyst of the Scientific Revolution as she stresses the importance of observational and experimental science to the modern intellect.